THU0080 PRECLINICAL CHARACTERIZATION OF TLL018, A NOVEL, HIGHLY POTENT AND SELECTIVE JAK1/TYK2 INHIBITOR FOR TREATING AUTOIMMUNE DISEASES. (2nd June 2020) - Liu, X.; Tan, F.; Liang, C.
Abstract : Background: Janus kinases (JAKs) are important regulators of intracellular responses triggered by many key proinflammatory cytokines and are clinically validated therapeutic targets for treating various autoimmune diseases. However, current approved JAK inhibitors failed to achieve maximal clinical benefit in part due to their unfavorable selectivity for individual JAKs such as JAK2 and/or JAK3, leading to dose-limiting toxicities or severe toxicities (e.g., thrombosis, anemia, immune suppression). Selective inhibition of JAK1 and/or TYK2 may minimize or avoid some of the toxicities and potentially offer a better therapeutic window for treating autoimmune diseases. No highly selective JAK1/TYK2 inhibitor has been reported to date. Objectives: Discovery of a highly selective JAK1/TYK2 inhibitor that maximally avoids JAK2 and JAK3 inhibition. We described preclinical characterization of a novel, highly potent and selective JAK1/TYK2 inhibitor TLL018 and its potential utility in treating autoimmune diseases such as rheumatoid arthritis (RA). Methods: Using predicting SAR, TLL018 was designed to achieve exquisite selectivity for both JAK1 and TYK2 while sparing JAK2, JAK3 and other human kinases. Its enzyme and cell activities, kinase selectivity, and in vivo efficacy were assessed in a battery of relevant enzyme, cell and whole blood assays, and in vivo arthritis animal models. Additional preclinical DMPK and toxicology studies were conducted to support its clinical development. Results: TLL018 is a highly potent and selective, orally bioavailable JAK1/TYK2 inhibitor against JAK1 (IC50 = 4 nM) and TYK2 (IC50 = 5 nM) as measured in in vitro kinase assays with ATP concentrations at individual Km. Its potency against JAK2 or JAK3 is greater than 1 µM. Profiling against a panel of over 350 human kinase showed that TLL018 is exclusively selective for JAK1 and TYK2, with ≥ 90-fold selectivity against all other kinases tested. TLL018 exhibited potent cellular activity for JAK1-mediated IL-6 signaling (IC50 = 0.6 µM) with greater than 100-fold selectivity against JAK2-mediated cytokine (e.g., TPO) signaling in human whole blood-based assays. Oral administration of TLL018 demonstrated dose-dependent efficacy in commonly studied rat adjuvant-induced arthritis (rAIA) model and mouse collagen-induced arthritis (mCIA) model. Significant inhibition of inflammation, bone resorption, splenomegaly and body weight change was observed in adjuvant-induced disease in rats. In addition, significant inhibition of inflammation, cartilage destruction, bone resorption and histological signs was demonstrated in collagen-induced arthritis in mice. Noticeably, TLL018 exhibited significant anti-inflammation activity at doses that only blocked JAK1 and TYK2 and exerted little inhibition of JAK2 and JAK3. In support of clinical development of TLL018, preclinical ADME and PK studies and IND-enabling toxicology and safety pharmacology studies were completed, confirming that TLL018 possesses excellent ADME and PK properties, and exhibits a clean on-target safety profile. Conclusion: TLL018 is a highly potent and selective JAK1/TYK2 inhibitor that demonstrated excellent efficacy and tolerability in relevant mouse and rat arthritis models. The collective data of its preclinical pharmacology, PK and toxicology showed a favorable pharmaceutical profile, further supporting its development for treating autoimmune diseases including RA. Clinical evaluation of TLL018 is ongoing. Disclosure of Interests: Xiangdong Liu Shareholder of: I own shares of TLL Pharmaceutical LLC, Employee of: I am employed by TLL Pharmaceutical LLC, Fenlai Tan Shareholder of: I own shares of TLL Pharmaceutical LLC, Employee of: I am employed by TLL Pharmaceutical LLC, Chris Liang Shareholder of: I own shares of TLL Pharmaceutical LLC, Employee of: I am employed by TLL Pharmaceutical LLC